2023
DOI: 10.3928/01913913-20220627-01
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Outcome of Pulled-in-Two Syndrome Associated With Strabismus Surgery

Abstract: Purpose: To report the incidence and outcomes of pulled-in-two syndrome during strabismus surgery and investigate the clinical features and management of the disease. Methods: The medical records of patients who underwent strabismus surgery and developed pulled-in-two syndrome between July 2013 and October 2020 were reviewed retrospectively. The demographic characteristics, intraoperative details (including surgery type and management), and subsequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A previous study reported 2 cases of pulled-in-two syndrome occurring during strabismus surgery for myopic strabismus fixus, in which lost muscles could not be recovered, but an acceptable appearance was achieved; therefore, they required no additional treatment. [ 8 ] However, our patient showed consequent exotropia of 45 prism diopters; therefore, MR muscle advancement was needed. Our experience highlights 2 crucial points: first, in myopic strabismus fixus, MR tenotomy might cause large overcorrection, and second, it is possible to find the pseudotendon with the slipped true tendon fixed to the sclera, even 3 months after the tenotomy.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study reported 2 cases of pulled-in-two syndrome occurring during strabismus surgery for myopic strabismus fixus, in which lost muscles could not be recovered, but an acceptable appearance was achieved; therefore, they required no additional treatment. [ 8 ] However, our patient showed consequent exotropia of 45 prism diopters; therefore, MR muscle advancement was needed. Our experience highlights 2 crucial points: first, in myopic strabismus fixus, MR tenotomy might cause large overcorrection, and second, it is possible to find the pseudotendon with the slipped true tendon fixed to the sclera, even 3 months after the tenotomy.…”
Section: Discussionmentioning
confidence: 94%